Non-Linear Structural Analysis of a Tensioner During Pipe Lay - Nor Zaihar, Naim Zafran (IRC, 2021)
Pipelay configurations in subsea include a J – Lay configuration for water depths of more than 500 feet and relies on a pipelay tensioner mounted on a near vertical tower on board a pipelay vessel.